The Aces of The Heart: Lived Experiences of Emergency Room Nurses in Managing Patients with Congestive Heart Failure and Its Implication to the Health Education - Ekpemandu, Chibueze Daniel (Gemilang Maju Publikasi Ilmiah (GMPI), 2024)
Nurses working in the ER and caring for CHF patients in the emergency room, where life-threatening illnesses are cared for, must always be highly skilled and proactive. Hence, a study aimed to explore the lived experiences of emergency room nurses caring for patients with congestive heart failure and its implications for health education as a phenomenological study. The Husserlian method was used among ten (10) participants chosen through purposeful sampling. The results show that most nurses are stressed, ill-experienced, and less skilled, which led to the conclusion that nurses need a charge-up to enhance both physical skills and relieve emotional stress. This implies that more training and skill acquisition seminars should be introduced to hospitals and institutional curricula to make ER nurses more competent and ready to face life-threatening conditions like CHF. Some implications to the health education including improved training programs, curriculum development, support systems in education, emphasis on disease knowledge, empathy and patient education, and building resilience.